Probabilistic reaction time analysis - Günzel, Mario; Ueter, Niklas; Chen, Kuan-Hsun; Brüggen, Georg von der; Chen, Jian-Jia (Technische Universität Dortmund, 2023)
In many embedded systems, for instance, in the automotive, avionic, or robotics domain, critical functionalities are implemented via chains of communicating recurrent tasks. To ensure safety and correctness of such systems, guarantees on the reaction time, that is, the delay between a cause (e.g., an external activity or reading of a sensor) and the corresponding effect, must be provided. Current approaches focus on the maximum reaction time, considering the worst-case system behavior. However, in many scenarios, probabilistic guarantees on the reaction time are sufficient. That is, it is sufficient to provide a guarantee that the reaction does not exceed a certain threshold with (at least) a certain probability. This work provides such probabilistic guarantees on the reaction time, considering two types of randomness: response time randomness and failure probabilities. To the best of our knowledge, this is the first work that defines and analyzes probabilistic reaction time for cause-effect chains based on sporadic tasks.
ACM transactions on embedded computing systems;22(5)
Keywords: reaction time; probability; end-to-end; sporadic; 004